2000
DOI: 10.1034/j.1600-065x.2000.17705.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐derived CXC chemokines: old players in new games

Abstract: Although platelet factor 4 (PF-4) and the beta-thromboglobulin (beta-TG) proteins represent the first chemokines to be discovered, their functional roles in host defense became clear only recently. Residing in platelets as storage proteins and becoming released into the blood at very high concentrations, these mediators appear to fulfill different and complementary tasks as first-line mediators in the recruitment and activation of leukocytes, as well in the regulation of tissue repair. Whereas both proteins ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
157
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(160 citation statements)
references
References 57 publications
2
157
0
1
Order By: Relevance
“…Although they are also secreted by other cells, platelets remain the most abundant and the most rapidly available source for these CXC-chemokines (17,18). It is well established that benzene lowers peripheral platelet counts (7)(8)(9), raising the possibility that our finding could be explained entirely or in part by a decrease in platelet counts among the exposed subjects.…”
Section: Confirmation Of Protein Biomarkersmentioning
confidence: 76%
See 1 more Smart Citation
“…Although they are also secreted by other cells, platelets remain the most abundant and the most rapidly available source for these CXC-chemokines (17,18). It is well established that benzene lowers peripheral platelet counts (7)(8)(9), raising the possibility that our finding could be explained entirely or in part by a decrease in platelet counts among the exposed subjects.…”
Section: Confirmation Of Protein Biomarkersmentioning
confidence: 76%
“…Two proteins were successfully purified and were positively identified as PF4 and CTAP-III. Both proteins are platelet-derived chemokines that are secreted from activated platelets practically simultaneously (17), raising the possibility that the observed differences in protein levels may have been driven by depressed platelet counts among benzene-exposed subjects. Several observations suggested that this was not the case.…”
Section: Discussionmentioning
confidence: 99%
“…These mediators induce PMN activation, chemotaxis, adhesion, degranulation of primary and secondary granules, and production of reactive oxygen species (38)(39)(40). TXA 2 , an important lipid mediator of platelets, is involved in platelet-neutrophil interactions (41) and plays a critical role in acid-induced ALI (7,42).…”
Section: Figurementioning
confidence: 99%
“…Activated platelets produce massive amounts of proinflammatory mediators and cross-talk with and activate different cells; in turn, platelets are activated by EC-derived proinflammatory substances binding to cognate receptors on the platelets' surface (49,50). Platelets' mediators are kept in the ␣-granules and dense body systems (51) and are promptly released upon activation, including histamine, serotonin, thromboxane A 2 , platelet-activating factor, PGE 2 and PGD 2 , TGF-␤, platelet-derived growth factor, multiple chemokines (RANTES, epithelia-derived neutrophil-activating 78, MCP-3, growth-related oncogene ␣, and MIP-1␣), IL-1␤, and thrombocidins, all of which target immune cells (46,52). Some of these products control vascular tone and permeability, but platelets also release trophic factors for ECs like vascular endothelial growth factor (VEGF), which promotes angiogenesis (53).…”
Section: Endothelial-platelet Interactionsmentioning
confidence: 99%